2020
DOI: 10.11648/j.sjac.20200802.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pollutant Levels in Water, Sediment and Winkles in Akani Obio Uruan River, Nigeria

Abstract: The levels of some trace metals (Cd, Cr, Cu, Pb and Zn) were quantified in water, sediment and two species of winkles (Pachymelania bryonensis and Pachymelania fusca mutans) in Akani Obio Uruan River from August to September 2018 (wet season) and February to March 2019 (dry season), using Varian spectra 100 atomic absorption spectrophotometer. The levels of some physicochemical parameters (temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), electrical conductivity (EC), total dissolved sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Fish samples: Fish samples were collected from the local fishermen fishing in the river using local fishing traps (Ikpa) set adjacent to the sampling locations at dusk and inspected at dawn [9]. Five medium sized fish samples were obtained very early in the morning and were put in a locally made aquarium and transported immediately to laboratory for further analysis [3]. Prior to analysis, the fish samples were washed with distilled water to remove loosely held particles before they were gutted and decapitated using stainless steel kitchen knife.…”
Section: Water Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Fish samples: Fish samples were collected from the local fishermen fishing in the river using local fishing traps (Ikpa) set adjacent to the sampling locations at dusk and inspected at dawn [9]. Five medium sized fish samples were obtained very early in the morning and were put in a locally made aquarium and transported immediately to laboratory for further analysis [3]. Prior to analysis, the fish samples were washed with distilled water to remove loosely held particles before they were gutted and decapitated using stainless steel kitchen knife.…”
Section: Water Samplesmentioning
confidence: 99%
“…Temperatures reaching extremes of heat or cold in aquatic environment could lead to survival of only a few organisms. Depletion of dissolved oxygen (DO) can lead to extinction of aquatic organisms [12].…”
Section: Physicochemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…''Water quality is continually threatened due to increasing inputs of the end products of anthropogenic activities and this attracts greater attention of government in the control of water pollution. This is because contaminants in air, soil or on land ultimately end up in the aquatic ecosystem through local precipitation, water run-off and leaching of rocks and solid wastes'' [8,9]. Investigation of the physicochemical parameters in water samples from Qua Iboe River, Ikot Ekpene stretch, Nigeria, revealed that the levels recorded were all within permissible limits set by World Health Organisation [1,6].…”
Section: Introductionmentioning
confidence: 98%